Usage of Solid Paraffin for Purification, Storage and Handling of Metallic Sodium - Yarman, A.; Beyribey, B.; Afsar, H. (ASIAN JOURNAL OF CHEMISTRY, 2010)
In this study, impure sodium was melted in molten solid paraffin. During this process heavier impurities in metallic sodium, such as sodium oxide and sodium hydroxide were collected under the molten sodium phase, while lighter impurities were collected over the sodium phase. After paraffin was cooled, solid sodium covered with paraffin was obtained.
Keywords: metallic sodium; purification; storage; handling; solid paraffin; Chemistry